SHORT WAVELENGTH AUTOMATED PERIMETRY CAN DETECT VISUAL FIELD CHANGES IN DIABETIC PATIENTS WITHOUT RETINOPATHY: AN OBSERVATIONAL STUDY - Dash, Snehalata; Beura, Lopamudra (Student’s Journal of Health Research Africa, 2025)
Background The purpose of the research was to assess the efficacy of SAP and SWAP-blue on yellow in detecting several changes taking place in the retinal sensitivity of the visual field in diabetic patients either with retinopathy or without retinopathy. Materials and methods This study was carried out at IMS and SUM Hospital, Bhubaneswar. The study was conducted for six months. Participants in the research who do not provide consent are not allowed to participate. Overall, 120 participants were included in the study. Results The Average age of participants in group 1 was 51.2±6.8, while that of group 2 was 53.7±7.4. A statistically significant difference in the duration of diabetes was seen between groups 1 and 2, with a p-value of less than 0.0001. SAP and SWAP were shown to be statistically significantly correlated in groups 1 and 2, with mean deviation p-values of 0.001 and <0.0001, respectively. Conclusion It has been found that compared to people with clinical retinopathy, diabetic patients without overt retinopathy are more likely to have aberrant findings picked up by the SWAP approach. Recommendation We recommend SWAP because SITA SWAP will prove to be useful for the early detection of glaucomatous conversion.